Diversidade morfoagronômica e ganhos de seleção em Butia capitata por abordagem multivariada e modelos mistos - Patrícia Nery Silva Souza (2022)
Butia capitata (Mart.) Becc., known as coquinho azedo, butiá azedo, has high nutritional value and multiple uses. However, the offer is made exclusively by extractivism. The domestication of the species is incipient, demanding accurate selection strategies to obtain superior genotypes. Thus, the objective was to evaluate genetic divergence, estimate genetic parameters and predict genetic values of morphoagronomic characters in progenies of B. capitata using different multivariate approaches and mixed models. Eighteen half-sib progenies were evaluated, in a randomized block design, with three replications and three plants per plot, spaced at 5 x 3 m. Between June 2019 and May 2021, 56 morphoagronomic traits were used in the diversity assessment. The Mahalanobis distance dissimilarity measure was used and the canonical variables analysis and hierarchical cluster analysis were used as multivariate approaches. The mixed models methodology was used to estimate genetic parameters considering quantitative morphoagronomic characters. The first and second canonical variables accounted for 71.85% of the total variation. The characteristics ratio of the length and width of the leaves, the length and width of the fruits, the leaf length, the number of bunches, the flavor and the color of the fruit were the ones that contributed the most to explain the variation between individuals. This analysis made it possible to highlight the divergence between the progenies. Heritability and coefficient of genetic variation indicated the possibility of successful selection of promising genotypes. Yield characteristics showed a positive correlation with plant height and leaf length. Progenies were selected that should be prioritized when choosing parents in a new selection cycle.